The long-term economic integration of resettled refugees in Canada: A comparison of Privately Sponsored Refugees and Government-Assisted Refugees - Kaida, Lisa; Hou, Feng; Stick, Max (Journal of Ethnic and Migration Studies, 2019)
Private refugee sponsorship has been an important Canadian policy initiative for 40 years. It is now attracting international attention as Europe grapples with an influx of refugees. However, no Canadian research has evaluated the long-term refugee economic integration associated with private sponsorship, in comparison to government assistance, using rigorous multivariate analysis. This study compares the economic outcomes of Privately Sponsored Refugees (PSRs) with those of Government-Assisted Refugees (GARs) using the Longitudinal Immigration Database, administrative data on virtually all immigrants and refugees arriving in Canada since 1980. Our regression analysis finds PSRs maintain higher employment rates and earnings than GARs up to 15 years after arrival when measurable compositional differences between the two groups are adjusted. The PSR advantage is particularly noticeable among less educated refugees. The findings suggest unmeasured factors (e.g. effectiveness of settlement policies, refugee selection processes, societal reception of refugees) may partly explain PSRs’ long-term economic advantage.
Keywords: Refugees; Canada; private sponsorship; economic integration; the Longitudinal Immigration Database